MODERNISASI PESANTREN TAHFIZ: Studi atas Pesantren Daarul Qur’an Tangerang - Mahfudh Fauzi; Ahmad Khoirul Fata (POTENSIA: Jurnal Kependidikan Islam, 2021)
The purpose of this study is to examine the Tahfiz al-Qur'an Curriculum and Tahfiz learning management at the “Daarul Qur'an” Islamic Boarding School of Tahfiz, Tangerang, Banten. This study is a qualitative research presented in a descriptive-analytical way. The data were collected through interviews, observations, and document studies. This research was conducted at the Tahfiz Daarul Quran Islamic Boarding School in Tangerang in 2018. The conclusion of this research is that Pesantren Tahfiz Daarul Qur'an Tangerang is managed by modern management while maintaining traditional values. In addition to tahfiz activities, students also get non-tahfiz learning. However, the right curriculum makes the students not divided in their concentration in memorizing the Qur'an. This actually encourages the development of the potential of students in other fields at the same time. However, there is still a need to improve the curriculum to further refine it